2009
DOI: 10.1200/jco.2009.22.4865
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Quantitative Polymerase Chain Reaction Detection of Minimal Residual Disease by Standardized WT1 Assay to Enhance Risk Stratification in Acute Myeloid Leukemia: A European LeukemiaNet Study

Abstract: Application of a standardized WT1 assay provides independent prognostic information in AML, lending support to incorporation of early assessment of MRD to develop more robust risk scores, to enhance risk stratification, and to identify patients who may benefit from allogeneic transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
423
2
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 398 publications
(446 citation statements)
references
References 45 publications
11
423
2
10
Order By: Relevance
“…Similarly, Galimberti et al (12) showed a higher probability of disease progression in AML patients presenting high WT1 levels, and recently, Nomdedeu et al (13) also confirmed the prognostic role of high WT1 levels at diagnosis in a larger study population. However, these data are in contrast with results reported by others where WT1 levels did not correlate with the outcome (8)(9)(10)14), thus suggesting a controversial role for WT1 expression at presentation. On the contrary, a greater agreement was found among groups that have used WT1 levels as a marker of minimal residual disease (MRD) in AML remission BMs (less than 5% of blast cells).…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, Galimberti et al (12) showed a higher probability of disease progression in AML patients presenting high WT1 levels, and recently, Nomdedeu et al (13) also confirmed the prognostic role of high WT1 levels at diagnosis in a larger study population. However, these data are in contrast with results reported by others where WT1 levels did not correlate with the outcome (8)(9)(10)14), thus suggesting a controversial role for WT1 expression at presentation. On the contrary, a greater agreement was found among groups that have used WT1 levels as a marker of minimal residual disease (MRD) in AML remission BMs (less than 5% of blast cells).…”
Section: Introductioncontrasting
confidence: 99%
“…Besides, WT1 is highly overexpressed in the BM or peripheral blood (PB) of a variety of leukemias, and these evidences support the role of WT1 as an oncogene in this subset (6,7). Increased levels of WT1 expression can be found in both acute lymphoblastic and acute myeloid leukemia (AML) although more frequently in AML (frequencies varying from 73% to 91%) (8)(9)(10). Following the discovery of overexpression of WT1, there has been growing evidence that the WT1 expression levels may have a prognostic role in AML.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 An added advantage of the qPCR method is that it can be standardized, as evidenced, for example, by multicenter efforts delineating the optimal control genes to include in the assays, as well as the definition of universally recognized protocols and primer designs. [3][4][5][6][7][8] Although these features constitute great advantages for the clinical integration of qPCR assays, major differences between individual laboratories in terms of variation in the qPCR procedures, together with differences in calculation of results and presentation of MRD data both in daily routine and in research, has hampered determination of the clinical use of MRD assessment in multicenter settings and the development of this technology to guide treatment approach. Given that this variability is a crucial limitation to the dissemination of this methodology, it was therefore decided under the auspices of the European LeukemiaNet (ELN) Minimal Residual Disease Work Package (WP12) to design a software package, which would enable individual centers conducting qPCR for MRD measurements to collect and express data in a standardized manner.…”
Section: Introductionmentioning
confidence: 99%
“…It is now broadly accepted as marker of minimal residual disease after chemotherapy and bone marrow transplantation in acute leukemias 5.…”
mentioning
confidence: 99%